2020
DOI: 10.2139/ssrn.3593121
|View full text |Cite
|
Sign up to set email alerts
|

Financial Factors and the Business Cycle

Abstract: We study how financial factors shape and interact with the U.S. business cycle through a unified empirical approach where we jointly estimate financial and business cycles as well as identify their underlying drivers using a medium-scale Bayesian Vector Autoregression. First, we show, both in reduced form and when we identify a structural financial shock, that variation in financial factors had a larger role in driving the output gap post-2000 and a more modest role pre-2000. Our results suggest that the finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…In the empirical analysis, in accordance with relevant works, such as Tamási and Világi (2011) or Berger et al (2020), two types of econometric models were used. On the one hand, Bayesian VAR (B-VAR) models were used to identify the effect caused by shocks in the financial system at the level of each state individually; on the other hand, panel data models were used to identify whether there were significant differences in impact caused by the level of development of the states.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the empirical analysis, in accordance with relevant works, such as Tamási and Világi (2011) or Berger et al (2020), two types of econometric models were used. On the one hand, Bayesian VAR (B-VAR) models were used to identify the effect caused by shocks in the financial system at the level of each state individually; on the other hand, panel data models were used to identify whether there were significant differences in impact caused by the level of development of the states.…”
Section: Methodology and Datamentioning
confidence: 99%
“…In the same area, a similar result was also discovered for the USA economy by Yan and Huang (2020) using wavelet functions but also VAR-type (vector autoregression) models. Berger et al (2020) analyzed the effect of financial factors on the economic cycle by means of Bayesian VAR models. The results of their study showed that the impact of financial factors on the output gap was much stronger in the period after 2000 than in the period before this year.…”
Section: Literature Reviewmentioning
confidence: 99%